The Analgesic Effect of Different Concentrations of Epidural Ropivacaine Alone or Combined With Sufentanil in Patients After Cesarean Section - Miao, Fangfang; Feng, Kunpeng; Feng, Xuexin; Fan, Long; Lang, Yu; Duan, Qingfang; Hou, Ruixue; Jin, Di; Wang, Tianlong (Frontiers in Pharmacology, 2021)
Background: Patients experience moderate-high intensity postoperative pain after cesarean section (CS). The aim of this study was to investigate the optimal concentrations of ropivacaine and sufentanil for use in controlling pain after CS. Methods: One hundred and seventy-four women undergoing elective CS were randomly allocated to four groups. Epidural analgesia was administered with 0.1% ropivacaine in the R1 group, 0.15% ropivacaine in the R2 group, a combination of 0.1% ropivacaine and 0.5 μg/ml of sufentanil in the R1S group, and a combination of 0.15% ropivacaine and 0.5 μg/ml of sufentanil in the R2S group (at a basal rate of 4 ml/h, bolus dose of 4 ml/20 min as needed). Pain scores (numerical rating scale [NRS]: 0–10 cm) at rest (NRS-R), during movement (NRS-M), and when massaging the uterus (NRS-U) were documented at 6 h and 24 h. We also recorded patient satisfaction scores, time to first flatus, motor deficits, and adverse drug reactions. Results: NRS (NRS-R, NRS-M, NRS-U) scores in the R2S group (2 [1–3], 4 [3–5], 6 [5–6], respectively) were lower than in the R1 group (3 [3–4], 5 [4–6], 7 [6–8], respectively) (P < 0.001, P < 0.05, P < 0.01, respectively) at 6 h; and patient satisfaction (9 [8–10]) was improved compared to the R1 group (8 [6–8]) (P < 0.01). The time to first flatus (18.7 ± 11.8 h) was reduced relative to the R1 group (25.9 ± 12.0 h) (P < 0.05). The time to first ambulation was not delayed (P > 0.05). However, the incidence of pruritus (4 [9.3%]) was increased compared to the R2 group (0 [0]) (P < 0.05) at 6 h, and the incidence of numbness (23 [53.5%], 23 [53.5%]) was increased compared to the R1 group (10 [23.3%], 10 [23.3%]) (all P < 0.01) at both 6 h and 24 h. Conclusion: Although we observed a higher incidence of pruritus and numbness, co-administration of 0.15% ropivacaine and 0.5 μg/ml of sufentanil administered epidurally optimized pain relief after CS, with treated subjects exhibiting lower NRS scores, shorter time to first flatus, and higher patient-satisfaction scores.